Characterization of Seawater Intrusion into Groundwater Aquifers Using the Electrical Resistivity Method in the Coastal Area of Tateli, North Sulawesi - Ferdy Ferdy; Dolfie Paulus Pandara; Maria Daurina Bobanto; Brian Benyamin Mambu (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to characterize the potential seawater intrusion in the aquifers of the coastal area of Tateli Beach, Manado. A geoelectrical resistivity survey was conducted using a dipole–dipole configuration with 48 potential electrodes spaced 10 m apart. The data were processed using RES2DINV software to generate two-dimensional resistivity sections. The resistivity values were correlated with groundwater quality data from nearby wells, particularly salinity and electrical conductivity. The modeling results revealed a low-resistivity zone (≤10 ohm·m), interpreted as a water-saturated aquifer down to a depth of approximately 20 m, overlain by a high-resistivity layer (≥5,000 ohm·m) acting as an aquifuge. Groundwater samples indicated salinity values of 0.01–0.02% and electrical conductivity ranging from 208 to 483 µS/cm, which are still classified as freshwater. In addition, a deeper aquifer was identified at around 50 m depth. These findings suggest that no significant seawater intrusion is currently present. The integration of resistivity imaging and groundwater quality analysis supports the conclusion that the aquifers remain preserved, although continuous monitoring is required to detect potential changes due to human activities and climate impacts.